Porque brincar é coisa séria: o lugar do lúdico nas práticas escolares e na formação do educador - Carleto, Eliana Aparecida (2000)
This work accords with Knowledge Research Area and School Practice from the Post-Graduation Course in Education of Universidade Federal de Uberlândia, more specifically with teachers' training. It aims to elucidate the place and meaning of playfulness in teacher training colleges. It also discusses the role of playfulness in children education and development based on the theories ofPiaget, Vygotsky, Chateau, Huizinga, Bandetand Sarazanas, Jacquin, Leifand Brunelle, and others'. It tries to verify how much the playfulness affects children's development Having studied all the theorists mentioned, the researcher suggests a discussion about the importance of playfulness in teacher training courses, more specifically, Cursos de Pedagogia (teacher training courses) which were broadly analyzed through a Brazilian historical study and recent discussions on academic and professional formation. Playfulness origin and related discussions during the eighties and nineties were recovered, and, having this goal in mind, the researcher took the Curso de Pedagogia da Universidade Federal de Uberlândia as the study object. She analyzed, deeply, its proposed syllabus, its disciplines' records, and, fínally, interviewed twenty students and teachers involved with the course, ffom both periods (morning and evening). More attention was given to the disciplines related, directly, to playfulness matters and its place on education. The analyzed disciplines are Psicologia da Educação (Education Psychology) , Princípios e Métodos da Alfabetização(MethoCi and Principies of Literacy), Didática G<?ra/(General Didactics), Didática e Metodologia da Língua Portuguesa e Literatura Brasileira na Educação Infantil e Séries Iniciais do Ensino Fundamental (Portuguese and Brazilian Literature Didactics and Methodology for Tnfant School and First Years of Junior School), Didática e Metodologia da Matemática na Educação Infantil e nas Séries Iniciais do Ensino Fundamental (Mathematics Didactics and Methodology for Infant School and First Years of Junior School), Didática e Metodologia de História e Geografia na Educação Infantil e nas Séries Iniciais do Ensino Fundamental (History and Geography Didactics and Methodology for Infant School and First Years of Junior School), Didática e Metodologia de Ciências na Educação Infantil e nas Séries Iniciais do Ensino Fundamental (Science Didactics and Methodology for Infant School and First Years of Junior School), Princípios e Métodos de Educação Infantil (Principies and Methods of Infant Education), and, fínally, Expressão Lúdica (Playfulness Expression). The data reveal how teachers and students see playful activities' role on teachers' formation. The analyzes emphasizes the importance of games, toys, and playing for children's cognitive socio-cultural development, and, therefore, these elements need for being present at teacher training colleges. Finally, this work verifies that these elements have not been present or discussed in the place studied and in the Brazilian scope. Ifs inferred that there is a lack to be filled and a challenged to be worked out through historical development of these courses.